Perilaku Masyarakat Terhadap Penyebaran Hoax Selama Pandemi Covid-19 Melalui Media di Indonesia: Tinjauan Literatur Sistematis - Trina Nur Faturohmah; Tamara Adriani Salim (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2022)
The spread of hoaxes is increasingly widespread in various media, causing changes in public behavior, especially during the COVID-19 pandemic. This research was conducted to see the development of publications related to public behavior towards hoaxes, the analysis related to the media for spreading hoaxes, and the impact of the spread of hoaxes on public behavior during the covid-19 pandemic This study uses the Systematic Literature Review (SLR) method by collecting literature related to the topics discussed then conducting an analysis of research on community behavior towards the spread of hoaxes during the COVID-19 pandemic through the media in Indonesia from 2020 to 2021. The results show that there are many the media used as a means of spreading hoaxes makes hoaxes more widespread, lack of understanding of information selection causes the spread of hoaxes to affect public behavior where people are anxious to take action during the covid-19 pandemic. This must be a concern for the government and the community, actions need to be taken to minimize the spread of hoaxes such as information literacy to the public regarding how to filter information from trusted sources.